Push-out test on the web opening shear connector for a slim-floor steel beam: Experimental and analytical study. (15th May 2018) - Hosseinpour, Emad; Baharom, Shahrizan; W. Badaruzzaman, Wan Hamidon; Al Zand, Ahmed W.
Highlights: Varied shape of web opening (WO) shear connectors were tested using push-out test. Highest direct shear capacity was obtained using square web opening shear connector. Optimum spacings of WO shear connectors are between 250 mm and 300 mm. Establishment of equation to predict ultimate shear resistance of web opening shear connectors. Abstract: In slim-floor construction, the web opening of the steel beam is proposed as WO shear connectors of different shapes; square (WSO), rectangular (WRO) and circular (WCO) connectors were considered to evaluate the ultimate shear strength, failure mode and ductility performance. Six push-out tests were conducted under static loading. Finite Element (FE) models using ABAQUS software were validated using test results, and then, further models were developed. The effective parameters include web thickness of the steel beam, opening size, compressive strength of the concrete slab and group arrangement for WO connectors. The test result indicates higher shear strength for the WSO shear connector compared with WRO and WCO. FE analysis presents notable shear achievement of WSO and WRO connectors because of the larger effective width of the square and rectangular openings incorporated with infill concrete. Thicker web steel beam associated with larger opening enhanced the compressive and tensile resistance area of the infill concrete in all cases. The effective spacing between group WCO shear connectors was found to be 250 mm, and it was found to be 300 mm for WSO and WRO to achieve maximum shear strength. Finally, the ultimate shear resistance of the WCO and WSO/WRO shear connectors were predicted and validated with COV of 0.032 and 0.021, respectively.